Low-level mosaic double trisomy involving trisomy 6 and trisomy 20 (48,XY,+6,+20) at amniocentesis without uniparental disomy (UPD) 6 and UPD 20 in a pregnancy associated with a favorable outcome - Chih-Ping Chen; Fang-Tzu Wu; Schu-Rern Chern; Peih-Shan Wu; Yen-Ting Pan; Meng-Shan Lee; Wayseen Wang (Elsevier, 2023)
Objective: We present low-level mosaic double trisomy involving trisomy 6 and trisomy 20 (48,XY,+6,+20) at amniocentesis without uniparental disomy (UPD) 6 and UPD 20 in a pregnancy associated with a favorable outcome. Case report: A 38-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 48,XY,+6,+20[2]/46,XY[15]. Repeat amniocentesis at 20 weeks of gestation revealed a karyotype of 48,XY,+6,+20[6]/46,XY[43], and simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (X,Y) × 1, (1-22) × 2 with no genomic imbalance. At 22 weeks of gestation, the woman underwent cordocentesis which revealed karyotype of 46,XY (60/60 cells). At 26 weeks of gestation, the woman underwent the third amniocentesis which revealed a karyotype of 48,XY,+6,+20[5]/46,XY[30], and simultaneous aCGH analysis on the DNA extracted from uncultured amniocytes revealed the result of arr (1-22) × 2, X × 1, Y × 1 without genomic imbalance. The parental karyotypes and prenatal ultrasound were normal. Polymorphic marker analysis using the DNAs extracted from uncultured amniocytes and parental bloods excluded UPD 6 and UPD 20. Interphase fluorescence in situ hybridization (FISH) analysis on 100 uncultured amniocytes detected double trisomy 6 and trisomy 20 in 10 cells, consistent with 10% (10/100 cells) mosaicism for double trisomy 6 and trisomy 20. The woman was encouraged to continue the pregnancy, and a phenotypically normal 3328-g male baby was delivered at 38 weeks of gestation. The cord blood, umbilical cord and the placenta had a karyotype of 46,XY (40/40 cells). Conclusion: Low-level mosaic double trisomy involving trisomy 6 and trisomy 20 at amniocentesis without UPD 6 and UPD 20 can be associated with a favorable fetal outcome.